Exercise does not improve insulin resistance and mitochondrial characteristics together. Issue 2 (9th December 2021) - Genders, Amanda J; Kuang, Jujiao; Marin, Evelyn C; Saner, Nicholas J; Botella, Javier; Jacques, Macsue; McConell, Glenn K; Andrade-Souza, Victor A; Chagolla, Javier; Bishop, David J
Abstract : The aim of this study was to investigate the relationship between mitochondrial content and respiratory function and whole-body insulin resistance in high-fat diet (HFD) fed rats. Male Wistar rats were given either a chow diet or an HFD for 12 weeks. After 4 weeks of the dietary intervention, half of the rats in each group began 8 weeks of interval training. In vivo glucose and insulin tolerance were assessed. Mitochondrial respiratory function was assessed in permeabilised soleus and white gastrocnemius (WG) muscles. Mitochondrial content was determined by the measurement of citrate synthase (CS) activity and protein expression of components of the electron transport system (ETS). We found HFD rats had impaired glucose and insulin tolerance but increased mitochondrial respiratory function and increased protein expression of components of the ETS. This was accompanied by an increase in CS activity in WG. Exercise training improved glucose and insulin tolerance in the HFD rats. Mitochondrial respiratory function was increased with exercise training in the chow-fed animals in soleus muscle. This exercise effect was absent in the HFD animals. In conclusion, exercise training improved insulin resistance in HFD rats but without changes in mitochondrial respiratory function and content. The lack of an association between mitochondrial characteristics and whole-body insulin resistance was reinforced by the absence of strong correlations between these measures. Our results suggest that improvements in mitochondrial respiratory function and content are not responsible for improvements in whole-body insulin resistance in HFD rats.